Penguatan Keterampilan Masyarakat dalam Manajemen Pakan Lele Dumbo pada Sistem Keramba Tancap di Desa Delima Jaya - Hazmi Ariefi; Alifa Rachmah; Angga Saputra, Deva; Josua Kristianto Sirait; Nisa Amalia; Putri Ayu Purnama Sari; Ratna Mey Kemalasari; Regita Akmal; Siti Nurhaliza; Willy Josevin Manihuruk; Yurida Sitanggang (PT. Cendekia Sapta Indonesia, 2025)
This community engagement program was carried out to address the challenges faced by fish farmers in Delima Jaya Village, Siak Regency, particularly the high feed costs and limited knowledge of feeding management for dumbo catfish. The main objective was to enhance farmers’ knowledge and skills in applying efficient feeding practices within the fixed net cage system. The program employed a combination of counseling, hands-on training, and intensive mentoring over one month, focusing on feeding rate (FR), feed conversion ratio (FCR), and survival rate (SR). The results indicated an improvement in participants’ ability to calculate and implement daily feeding doses accurately, leading to more efficient feed utilization, reduced operational costs, and improved aquaculture productivity. This program contributed significantly to strengthening community capacity in aquaculture management and has the potential to be replicated by other farmer groups in the region to ensure sustainability.